2022
DOI: 10.1111/dth.15746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation and analysis of skin reactions caused by COVID‐19 vaccination

Abstract: The novel coronavirus disease 2019 vaccination is now an essential strategy for controlling the COVID-19 epidemic. This study included 132 cases of adverse skin reactions after the injection of COVID-19 vaccination from January 2021 to January 2022. The rate of adverse skin reactions after the 1st, 2nd, and 3rd doses of the COVID-19 vaccine were 52%, 40%, and 8% of total adverse skin reactions, respectively. The Urticaria-like rash was the most common manifestation of all adverse skin reactions, accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“… 10 One study showed that eczema-like rashes accounted for 27.27% of all adverse skin reactions. 11 Generalized eczema is an extremely rare condition with a complex mechanism of occurrence and development that is related to immune system dysfunction. The characteristics of a prolonged onset period, frequent recurrence, and difficulty in finding a cure seriously affect the quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
“… 10 One study showed that eczema-like rashes accounted for 27.27% of all adverse skin reactions. 11 Generalized eczema is an extremely rare condition with a complex mechanism of occurrence and development that is related to immune system dysfunction. The characteristics of a prolonged onset period, frequent recurrence, and difficulty in finding a cure seriously affect the quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatology Review/Przegląd Dermatologiczny 2023/4 et al reported recurrence of lichen planus after the first injection of COVID-19 vaccine in 1 patient as well as after the second injection in 1 patient [44].…”
Section: Discussionmentioning
confidence: 99%
“…Li i wsp. opisali także nawrót liszaja płaskiego po pierwszej dawce szczepionki przeciw COVID-19 u jednego pacjenta oraz po drugiej dawce u innego pacjenta [44].…”
Section: Articles That Reported the Onsetunclassified